Recent Advances in Multimedia Signal Processing and Communications - Grgic, Mislav; Delac, Kresimir; Ghanbari, Mohammed (Studies in Computational Intelligence,, 2009)
The rapid increase in computing power and communication speed, coupled with computer storage facilities availability, has led to a new age of multimedia applications. Multimedia is practically everywhere and all around us we can feel its presence in almost all applications ranging from online video databases, IPTV, interactive multimedia and more recently in multimedia based social interaction. These new growing applications require high-quality data storage, easy access to multimedia content and reliable delivery. Moving ever closer to commercial deployment also aroused a higher awareness of security and intellectual property management issues. All the aforementioned requirements resulted in higher demands on various areas of research (signal processing, image/video processing and analysis, communication protocols, content search, watermarking, etc.). This book covers the most prominent research issues in multimedia and is divided into four main sections: i) content based retrieval, ii) storage and remote access, iii) watermarking and copyright protection and iv) multimedia applications.